Effect of enamelsurface treatment on bond strength of fluorosed teeth - Rivera Cerdas, Andrea (2014)
The purpose of this study was to evaluate bond strength in 48 dental premolar with fluorosis using prepared enamel with 3 sof-lex ® discs with different degrees of abrassiveness, applying a conventional adhesive system PQ1® provided by Ultradent Products. Four groups, each one with 12 premolars were elected randomly and cut by an ISOMET machine. The samples were stored at 100% relative humidity at 37° C for 7 days before the test applying tension at the speed of 0.1 cm/min until it broke in a Tinius Olsen Testing Machine. The findings of this study showed that the preparation of enamel fluorosis may be critical for efficient adhesion to the enamel surface, especially using Soflex discs. This study showed that the preparation of enamel in teeth with dental fluorosis was best when the roughness of enamel the surface increased, thus obtaining higher bond strength using PQ1.